Indentation creep deformation behavior of local zones for X70 girth weld. (October 2022) - Cao, Jun; Wang, Ke; Ma, Weifeng; Ren, Junjie; Nie, Hailiang; Dang, Wei; Liang, Xiaobin; Yao, Tian; Zhao, Xiaohan
Abstract: Creep failure of in-service pipes is a fundamental engineering issue. Since the girth weld joint is a weak link in the pipeline, the creep deformation behavior of the girth weld must be carefully researched. This research sheds light on determining the local creep properties of girth welds. The creep deformation behavior of local zones for the X70 girth weld was studied using nanoindentation creep experiments with maximum nano-indenter loads of 10 mN, 50 mN, and 100 mN. The load dependency and creep mechanism of local zones for the X70 girth weld were investigated through creep properties such as creep strain rate, creep stress, creep stress index, and strain rate sensitivity index. In addition, the microstructures of base material (BM), root welding zone (RWZ), and heat-affected zone (HAZ) were studied to determine the differences in creep properties for the girth weld's local zones. The creep displacement of BM, RWZ, and HAZ follow the RWZ > BM > HAZ sequence as the maximum load increases. The creep stress, on the other hand, exhibits HAZ > RWZ > BM sequence. Furthermore, RWZ and HAZ have a higher load dependency of creep stress index and strain rate sensitivity than BM. Graphical abstract: Image 1 Highlights: The creep deformation behavior of local zones for the X70 girth weld was studied. This research sheds light on determining the local creep properties of girth welds. The load dependency of local zones for the X70 girth weld was studied. The difference in local zones of load dependency for creep properties was studied.